Mathematics for secondary education project (Matem-UNA): perception of students about of the courses received and the profesional careers they selected for higher education - Alfaro Arce, Ana Lucía (2013)
This paper summarizes the opinions of students who have enrolled in the Precalculus course offered by the MATEM project. The aim is to systematize the views expressed by the students enrolled in MATEM, which are related to general aspects of the project, and also to know the professional areas these students select when entering to the university. The information for this study was collected through two questionnaires administered to the participating students during 2005-2009. The most relevant results are the following: the students listed benefits from MATEM such as the opportunity to practice for their Mathematics test (Ministry of Education exam), obtaining new knowledge and developing mathematical and reasoning skills. Most students would recommend others to participate in the project. Regarding the careers that students pursue, it was found a preference for higher studies in public universities at Costa Rica; these majors include mathematics courses in their curriculum (Engineering, Economics, Statistics, Medicine, among others).